Gender Diversity, Corporate Social Responsibility, Return on Asset, and Leverage on the Corporate Tax Aggressiveness of Manufacturing Companies in Indonesia - Wulandari, Diah Ayu Putri; Tjahjono, Mazda Eko Sri; Ismawati, Iis; Mulyanah (Yayasan Ilomata, 2024)
This research attempts to ascertain how gender diversity, corporate social responsibility, return on assets, and leverage affect tax aggressiveness. The novelty and contribution of this research is that these four variables have not all been studied for their influence on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Previous studies with different company sectors and periods have also proven mixed research results. The total research population was 170 companies, and 86 sample companies were selected using the purposive sampling technique. The research period was four years, so 344 research data were collected. Then, 62 research data were outlier data, so the final number of samples to be tested was 282 research data. IBM SPSS 25 was used to conduct a multiple linear regression analysis approach. This study will present the results of descriptive data analysis and parametric statistical analysis, which include classical assumption tests, hypothesis tests, and coefficient of determination tests. The research conclusion shows that gender diversity and leverage have a negative effect on tax aggressiveness. The presence of women on the company's board will help the supervisory function so that the level of corporate tax aggressiveness can decrease. In addition, the increase in corporate leverage will reduce the tax burden so that the level of corporate tax aggressiveness will also decrease. Meanwhile, corporate social responsibility and return on assets positively affect tax aggressiveness. Companies carry out the fulfillment of CSR obligations only to obtain a good image in order to cover up irresponsible actions, such as tax avoidance. In addition, profitable businesses may make the most of their resources to optimize their tax planning to reduce their tax burden and raise their level of tax aggressiveness.